Bamboo vinegar liquid probiotics for replacing antibiotic on the performance and meat quality of broiler chicken (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
A study was conducted to investigate the effects of bamboo vinegar liquid with beneficial microbes (probiotics), BVLP on growth performance, meat composition, and thiobarbituric acid (TBA) value. A total of 175 one day old Ross broiler chicks were distributed to 5 treatments having 5 replications with 7 chicks in each, following a completely randomized design. The treatments were: control (basal), antibiotic (basal+30 ppm Oxytetracycline), bamboo vinegar liquid probiotics (basal+0.2%, basal+0.4% and basal+0.8%).   Significantly lowest feed intake was recorded in 0.4% BVLP compared to 0.8% BVLP group although highest weight gain was observed in 0.2% BVLP among the BVLP groups(P